Maternal PlGF and sFlt-1 are Associated with Low Birth Weight and/or Small-for-Gestational Age Neonates in Pregnancy with or without Preeclampsia - Luo, Wenbo; Tang, Pingping; Lv, Yan; Song, Yijun; Hu, Huiying; Gao, Jinsong; Liu, Juntao (American Journal of Perinatology Reports, 2025)
To evaluate the association of PIGF and sFlt-1 with low birth weight and/or small-for-gestational age neonates in pregnancy with or without preeclampsia.Singleton pregnancies with sFlt-1/PlGF tested were included and set into four groups for case–control analysis. Distribution of sFlt-1/PlGF, sFlt-1, PlGF, and PGF% were evaluated, Kruskal–Wallis test and Mann–Whitney U test were adopted for significance analysis.Maternal sFlt-1/PlGF, PlGF, PlGF%, and sFlt-1 were statistically associated with low birth weight and/or small-for-gestational age in pregnancy complicated or uncomplicated with preeclampsia. A significant difference was shown on sFlt-1/PIGF (p = 0.0082), PIGF% (p = 0.0326), PIGF (p = 0.0128), and sFlt-1 (p = 0.0469) in pregnancy with small-for-gestational age and/or low birth weight neonates. A significantly higher median of sFlt-1/PlGF (448 vs. 61.6, p < 0.0001) and sFlt-1 (15499 vs. 3226, p < 0.0001), a significantly lower median of PlGF (33.92 vs. 115.2, p < 0.0001) and PlGF% (−76.63 vs. −20.31, p < 0.0001) were demonstrated, respectively, when preeclampsia with small-for-gestational age and/or low birth weight neonates was compared with preeclampsia with normal birth weight neonates. No significant difference was demonstrated between low birth weight and small-for-gestational age on sFlt-1/PlGF, PlGF, PlGF%, and sFlt-1.sFlt-1/PlGF seems to be a promising biomarker in predicting low birth weight and/or small-for-gestational age neonates in pregnancy with or without preeclampsia.
Keywords: placental growth factor; soluble fms-like tyrosine kinase-1; low birth weight; small-for-gestational age